Construction of a novel two-dimensional AgBiO3/BiOBr step-scheme heterojunction for enhanced broad-spectrum photocatalytic performance. Issue 32 (18th July 2022) - Lu, Jianhong; Bie, Junhong; Fu, Shuai; Wu, Jiaqi; Huang, Qiang; He, Pengli; Yang, Zhe; Zhang, Xiuji; Zhu, Huijie; Deng, Peiyuan
Abstract : Efficient S-scheme heterojunction photocatalysts were prepared through in situ growth of AgBiO3 on BiOBr. Abstract : Efficient S-scheme heterojunction photocatalysts were prepared through in situ growth of AgBiO3 on BiOBr. The self-assembled hierarchical structure of AgBiO3 /BiOBr was formed from flower-like AgBiO3 and plate-like BiOBr. The optimized AgBiO3 /BiOBr heterojunction possessed excellent visible-light photocatalytic degradation efficiency (83%) for ciprofloxacin (CIP) after 120 min, with 1.46- and 4.15-times higher activity than pure AgBiO3 and BiOBr, respectively. Furthermore, the removal ratio of multiple organic pollutants including tetracycline, Rhodamine B, Lanasol Red 5B and methyl orange was also investigated. Environmental interference experiments demonstrated that high pollutant concentrations, low photocatalyst dose and the addition of ions (SO4 2−, PO4 3−, HPO4 2−, H2 PO4 − ) inhibited the photocatalytic activities. Subsequently, a simultaneous degradation experiment showed the competitive actions between CIP and RhB for radicals, decreasing the photocatalytic activity of CIP. Furthermore, trapping and electron spin resonance experiments showed that h + and ˙O2 − played a certain role in the degradation process and that ˙OH acted as assistant.